Effects of Seed Storage Periods on Electrical Conductivity of Seed Leakage, Germination and Field Emergence Percentage in Common Bean (Phaseolus vulgaris L.) - PALABIYIK, BURCU; PEKSEN, ERKUT (Asian Journal of Chemistry, 2010)
This study was carried out to determine the effects of seed storage at + 4 °C for 8, 20, 32 and 44 months on electrical conductivity of seed leakage, germination and field emergence percentages in common bean (Phaseolus vulgaris L.). The seeds of common bean cvs Karacasehir-90, Sahin-90 and Yunus-90 were used in present investigation. Field experiments were conducted under three diverse environmental conditions (E1, E2 and E3) for soil texture, seedbed moisture content at sowing time, soil and air temperature during the seedling emergence and also total rainfall at pre- and postsowing periods in Samsun and Sinop provinces, Turkey, in year 2004. In addition, germination speed (GS) and germination power percentage (GP), the length of seedling emergence periods (SEP) and electrical conductivity (EC) of seed leakage were determined. Environments showed significant differences for field emergence (FE) (p < 0.05) and SEP (p < 0.01). In E1, unfavourable environmental conditions at the germination and seedling emergence stage significantly reduced FE percentage (60.11 %) and extended SEP (14.07 d), when compared with E2 (81.00 % and 8.64 d) and E3 (61.78 % and 8.36 d). Bean cultivars were not different in terms of GS, GP and the length of SEP, while they were different for FE and EC values. GS, GP, FE and EC ranged from 89.69-94.06 %, 91.88-96.56 %, 63.12-72.12 %, 26.72-36.42 μS cm-1 g-1 among cultivars, respectively. GS, GP, FE, EC and SEP were affected by the storage periods. Lower GS, GP and FE (p < 0.01) were determined in seeds stored for 44 months than that in the others due to reduction in seed viability with the extending time of storage. In addition, seed storage of 44 months had the longest SEP and highest EC values. Strong relationships were found between EC and GS (r = -0.9316**), EC and GP (r = -0.9186**), EC and FE (r = -0.7660**). Study results showed that common bean seeds could be stored safely at + 4 °C up to 32 months without a significant reduction occurred in their viability.